2022
DOI: 10.1007/s00415-022-11126-7
|View full text |Cite
|
Sign up to set email alerts
|

A SUMO4 initiator codon variant in amyotrophic lateral sclerosis reduces SUMO4 expression and alters stress granule dynamics

Abstract: Background Recent evidence points toward a role of the small ubiquitin-like modifier (SUMO) system, including SUMO4, in protecting from stress insults and neurodegeneration, such as the progressive motor neuron disease amyotrophic lateral sclerosis (ALS), e.g., by regulating stress granule (SG) dynamics. Here, we investigated whether SUMO4 variants play a role in ALS pathogenesis. Methods Whole-exome or targeted SUMO4 sequencing was done in 222 unrelated E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…in neuronal development or learning and memory(Ripamonti et al, 2020). Furthermore, SUMOylation has been linked with various brain disorders, including Autism Spectrum Disorder, Epilepsy, Schizophrenia, and neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and Amyotrophic Lateral Sclerosis (Bernstock et al, 2018; Krumova and Weishaupt, 2013; Osmanovic et al, 2022; Rousseaux et al, 2016). However, despite a clear connection with neuronal function and dysfunction, SUMOylation has remained enigmatic due to technical challenges and limitations for studying this modification (Daniel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…in neuronal development or learning and memory(Ripamonti et al, 2020). Furthermore, SUMOylation has been linked with various brain disorders, including Autism Spectrum Disorder, Epilepsy, Schizophrenia, and neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and Amyotrophic Lateral Sclerosis (Bernstock et al, 2018; Krumova and Weishaupt, 2013; Osmanovic et al, 2022; Rousseaux et al, 2016). However, despite a clear connection with neuronal function and dysfunction, SUMOylation has remained enigmatic due to technical challenges and limitations for studying this modification (Daniel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Like ubiquitination, this modification is important for regulating SG disassembly, especially in relation to ALS genetic contexts. For example, SUMO4 mutations identified in ALS patients cause decreased SUMO4 mRNA and protein expression and are associated with significantly more SGs per patient fibroblast in response to oxidative stress . These mutations also resulted in reduced SUMOylation of the ALS-associated protein VCP, suggesting a possible causative link, as SUMOylation was previously shown to direct VCP recruitment to SGs, where it serves a key role in SG disassembly .…”
Section: Regulation Of Stress Granule Dynamicsmentioning
confidence: 98%
“…For example, SUMO4 mutations identified in ALS patients cause decreased SUMO4 mRNA and protein expression and are associated with significantly more SGs per patient fibroblast in response to oxidative stress. 205 These mutations also resulted in reduced SUMOylation of the ALS-associated protein VCP, suggesting a possible causative link, as SUMOylation was previously shown to direct VCP recruitment to SGs, where it serves a key role in SG disassembly. 206 In fact, mutations aimed at obstructing SUMO attachment to VCP directly impaired the disassembly of SGs.…”
Section: Phosphorylationmentioning
confidence: 99%
“…A loss-of-function mechanism has also been associated with the DnaJ heat shock protein family member C7 (DNAJC7), which has been identified as a genetic risk factor for ALS according to a large-scale WES study [50]. Indeed, a functional study has recently shown reduced protein levels in ALS patients carrying a p.R156X variant, suggesting a role of DNAJC7 in the regulation of protein misfolding, which is a major molecular pathology in ALS, through its interaction with HSP90 and HSP70 [51].…”
Section: Proposed Disease Mechanismsmentioning
confidence: 99%